2020
DOI: 10.2991/jegh.k.200102.003
|View full text |Cite
|
Sign up to set email alerts
|

Care-Related Quality of Life of Caregivers of Beta-Thalassemia Major Children: An Epidemiological Study in Eastern India

Abstract: Caregivers are the persons who provide care at the time of distress or illness. They face many stress and strain to provide the best possible medical care for their children. There are very few studies that explored the care-related quality of life (CarerQoL) of the caregivers of thalassemic children and its correlates. With this background, the current study was designed to explore the CarerQoL of the caregivers of β -Thalassemia Major ( β -TM) children and its va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Naturally, study participants were mostly from rural areas and their educational level were mostly up to primary level and most of them were home maker and belonged to lower middle and middle SES Class. Present study results were almost similar to the study conducted by Biswas et al 11 Diagram 1 showed that, 60.3% of the study participants had favourable PCS of health. But in case of MCS of health we had found that, majority (64.7%) of the caregivers were having unfavourable MCS.…”
Section: Resultssupporting
confidence: 90%
“…Naturally, study participants were mostly from rural areas and their educational level were mostly up to primary level and most of them were home maker and belonged to lower middle and middle SES Class. Present study results were almost similar to the study conducted by Biswas et al 11 Diagram 1 showed that, 60.3% of the study participants had favourable PCS of health. But in case of MCS of health we had found that, majority (64.7%) of the caregivers were having unfavourable MCS.…”
Section: Resultssupporting
confidence: 90%
“…They experienced the shortages of medications and exhibited adverse lifestyle behaviours leading to declined health (Yan et al, 2020). It is evident that healthy behaviours and strategies can modify and maintain wellness components amongst patients with beta thalassemia major (Biswas et al, 2020). The long-lasting impact of the pandemic on health behaviours, and the possibility of several COVID-19 peaks, emphasise the need for creative and evolving, multilevel approaches to assist these patients to be able to adapt healthy behaviours and prevent disease comorbidities and COVD-19 (Eleftheriou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Life-training skills, self-care management and psychological treatment have been suggested as healthcare management strategies to people with TDTs to lead an independent life with good QOL and health [32][33][34]. These should start during their childhood and perhaps be extended to their caregivers as indicated by other studies [35,36]. With proper training and guidance, they may fare as well as the people without the disease [37].…”
Section: Multiple Linear Regression a (Coefficient (95% Ci))mentioning
confidence: 99%